Clonal hematopoiesis and cardiovascular diseases: role of JAK2V617F. Issue 1 (January 2023) - Misaka, Tomofumi; Kimishima, Yusuke; Yokokawa, Tetsuro; Ikeda, Kazuhiko; Takeishi, Yasuchika
Highlights: Age-related clonal hematopoiesis is common in humans. JAK2 V617F is one of the most relevant gene mutations in clonal hematopoiesis. Clonal hematopoiesis with JAK2 V617F is associated with cardiovascular diseases. Identification of JAK2 V617F-indivisuals is an approach to stratify the event risk. JAK2 V617F-clonal hematopoiesis is a therapeutic target for cardiovascular diseases. Summary: Bone marrow-derived hematopoietic and immune cells play important roles in the onset and progression of cardiovascular diseases. Recent genetic analyses have discovered that clonal expansion of bone marrow hematopoietic stem/progenitor cells carrying somatic gene mutations is common and is increasing with age in healthy individuals who do not show any hematologic disorders, termed as clonal hematopoiesis. It is emergingly recognized that clonal hematopoiesis is a significant risk factor for cardiovascular diseases rather than a cumulative incidence risk of blood cancers. JAK2 V617F, a gain-of-function mutation, has been identified as one of the most important mutations in clonal hematopoiesis as well as the most frequent driver mutation in myeloproliferative neoplasms. Hematopoietic cell clones harboring JAK2V617F are causally associated with the pathogenesis of cardiovascular diseases. Here, we will review the key of JAK2 V617F-mediated clonal hematopoiesis including identification, prevalence, and biological impacts, linking to cardiovascular diseases and the related mechanisms. Clonal hematopoiesis with JAK2 V617F may be a novel therapeutic target for cardiovascular diseases, connected to precision medicines by detecting its presence. Graphical abstract: Image, graphical abstract